2017
DOI: 10.1007/s10637-017-0451-2
|View full text |Cite
|
Sign up to set email alerts
|

Human mass balance study and metabolite profiling of 14C-niraparib, a novel poly(ADP-Ribose) polymerase (PARP)-1 and PARP-2 inhibitor, in patients with advanced cancer

Abstract: SummaryNiraparib is an investigational oral, once daily, selective poly(ADP-Ribose) polymerase (PARP)-1 and PARP-2 inhibitor. In the pivotal Phase 3 NOVA/ENGOT/OV16 study, niraparib met its primary endpoint of improving progression-free survival (PFS) for adult patients with recurrent, platinum sensitive, ovarian, fallopian tube, or primary peritoneal cancer in complete or partial response to platinum-based chemotherapy. Significant improvements in PFS were seen in all patient cohorts regardless of biomarker s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…A plasma sample (0–120 h) was obtained by pooling plasma at each time point of a volume proportional to the time interval used for calculating the area under the concentration–time curve (AUC) (AUC 0–120 h pool) for each subject. Moreover, three plasma samples at time periods 0–0.0833 h, 0.133–2 h and 4–120 h were obtained by pooling equal volumes of plasma across individuals at the same time point 10–12 . Urine samples (0–168 h) were pooled at an equal percentage of collection volume to obtain one pooled sample for each subject.…”
Section: Methodsmentioning
confidence: 99%
“…A plasma sample (0–120 h) was obtained by pooling plasma at each time point of a volume proportional to the time interval used for calculating the area under the concentration–time curve (AUC) (AUC 0–120 h pool) for each subject. Moreover, three plasma samples at time periods 0–0.0833 h, 0.133–2 h and 4–120 h were obtained by pooling equal volumes of plasma across individuals at the same time point 10–12 . Urine samples (0–168 h) were pooled at an equal percentage of collection volume to obtain one pooled sample for each subject.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, pharmacokinetics differs from one PARPi to another. For example, niraparib is not metabolized by hepatic cytochromes and has less potential for drug-drug interactions [ 43 , 44 ]. Furthermore, the absorption is not influenced by food [ 42 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…Studies with radiolabeled niraparib have shown a recovery of 47.5% of the drug in urines and 38.8% in feces [ 44 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…The t ½ of total 14 C-radioactivity was longer than the t ½ of 14 C-niraparib, which further confirms metabolite formation. Metabolites have been identified and quantified previously [ 16 ]. Besides niraparib, the main moiety in circulation, the amide-hydrolysed niraparib metabolite (M1) and its glucuronide (M10) were also substantially present in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…A mass balance study in humans using radiolabelled niraparib investigated the amount of niraparib and niraparib-related compounds excreted in urine and in faeces [ 16 ]. Of the total dose orally administered, approximately 90% was recovered in excreta, with approximately 20% recovered as the parent compound in faeces.…”
Section: Discussionmentioning
confidence: 99%